PENGARUH TINGKAT STRES TERHADAP MEKANISME KOPING PASIEN KANKER BERBASIS MANAJEMEN TERAPI KANKER - Werdani, Yesiana Dwi Wahyu (Universitas Tribhuwana Tunggadewi, 2020)
The management of cancer therapy is useful to improve the survival of cancer patients, but it has a physical impact on various functions of the body's organs. It can lead to stress and affect individual coping mechanisms. The aim of this study was to analyze the effect of stress levels on coping mechanisms of cancer patients based on cancer therapeutic management. This study used a mix method design and sequential explanatory approach. The population was cancer patients at the Indonesian Cancer Foundation, East Java Branch, Surabaya. The number of sample were 32 patients taken by total sampling method. The instrument used perceived stress scale and coping strategies inventory short form. The result of ordinal regression test and nagelkerle's pseudo R-Square in chemotherapy group 0.013 and R 0.621, in radiation group 0.016 and R 0.597, in chemoradiotherapy group 0.010 and R 0.737. It means that stress levels has a significant effect on individual coping mechanisms in all cancer therapeutic management groups. On the qualitative results showed that stress and maladaptive coping mechanisms caused by side effects of therapy, financial, relationships with caregiver was less harmonious, less able to think positively. The complexity of therapeutic stressors and the presence of poorly managed of external factors made respondents more likely to have maladaptive coping mechanisms.